Chronic, Combined Cardiac and Renal Dysfunction Exacerbates Renal Venous Pressure-Induced Suppression of Renal Function in Rats - Hamza, Shereen M.; Huang, Xiaohua; Zehra, Tayyaba; Zhuang, Wenqing; Cupples, William A.; Braam, Branko (Frontiers in Physiology, 2022)
Background & Objective: Increased renal venous pressure (RVP) is common in combined heart and kidney failure. We previously showed that acute RVP elevation depresses renal blood flow (RBF), GFR and induces renal vasoconstriction in the absence of changes in blood pressure in healthy rats. We used our established rodent model of chronic combined heart and kidney failure (H/KF) to test whether RVP elevation would impair cardiovascular stability, renal perfusion and exacerbate renal dysfunction. Methods: Male rats were subjected to 5/6 nephrectomy (SNx or Sham) and 6% high salt diet followed 7 weeks later by ligation of the left anterior descending coronary artery (CL or Sham). Experimental groups: CL+SNx (n=12), Sham CL+SNx (n=9), CL+ Sham SNx (n=6) and Sham Control (n=6). Six weeks later, anesthetized rats were subjected to an acute experiment whereupon mean arterial pressure (MAP), heart rate (HR), RVP, RBF and GFR were measured at baseline and during elevation of RVP to 20-25 mmHg for 120 min. Results: Baseline MAP, HR, RBF and renal vascular conductance (RVC) were comparable among groups. Baseline GFR was significantly depressed in CL+SNx and Sham CL+SNx groups compared to Sham Control and CL+Sham SNx groups. Upon RVP increase, MAP and HR fell in all groups. Increased RVP exacerbated the reduction in RBF in CL+SNx (-6.4±0.9 mL/min) compared to Sham Control (-3.7±0.9 mL/min, p<0.05) with intermediate responses in Sham CL+SNx (-6.8±1.3 mL/min) and CL+Sham SNx (-5.1±0.4 mL/min) groups. RVP increase virtually eliminated GFR in CL+SNx (-99±1%), Sham CL+SNx (-95±5%) and CL+Sham SNx (-100%) groups compared to Sham Control (-84±15% from baseline; p<0.05). Renal vascular conductance dropped significantly upon RVP increase in rats with HF (CL+SNx: -0.035±0.011; CL+Sham SNx: -0.050±0.005 mL/min·mmHg-1, p<0.05) but not Sham CL+SNx (-0.001±0.019 mL/min·mmHg-1) or Control (-0.033± mL/min·mmHg-1). Conclusions: Chronic combined heart and kidney failure primarily impairs renal hemodynamic stability in response to elevated RVP compared to healthy rats.